A review on medicinal plants with supposed biological activities for the endogenous management of the COVID‐‐‐‐19 pandemic in Benin, Togo, Ghana, Burkina-Faso and Cape Verde - Dougnon, Tamègnon Victorien; Amadou, Affousath; Legba, Boris Brice; Agbodjento, Eric; AGBANKPE, Alidehou Jerrold; Rocha, Diara; Ayi, Irène; Azonbakin, Simon; Diallo, Aboudoulatif; Bonkongou, Isidore; AGBANGLA, Clément; Alitonou, Guy Alain (My University, 2022)
The rapid emergence of the coronavirus infection worldwide since December 2019 (Covid-19) has incited the search for therapeutic solutions following different approaches. The use of natural remedies is an alternative solution to strengthen immunity and fight and prevent Covid-19. This study aimed to review the medicinal plants used against Covid-19 infection or the symptoms of Covid-19 in Benin, Togo, Ghana, Burkina Faso and Cape Verde. Data were collected from databases such as PubMed, Google Scholar, Science Direct and Scopus. In total, 152 medicinal plants belonging to 53 botanical families were identified. The most represented families were Leguminosae, Rubiaceae, Apocynaceae, Combretaceae and Compositae. Fever, cough, fatigue, stomach ache, sore throat and headache are the main symptoms of Covid-19 treated by these plants. Leaves, roots, bark and fruits are the most used plant organs. Scientific validation of some medicinal plants recorded demonstrated their antiviral, anti-inflammatory, antioxidant and anti-malarial properties, thus justifying their use in the management of Covid-19. In this review, we provide scientific literature highlighting the significant contribution of ethnobotany and pharmacology to the management of Covid-19. In addition, future studies can be conducted on these plants to gain more scientific data on their pharmacological activities and to accelerate the development of traditional medicine for the treatment of Covid-19.
Keywords: Ethnobotany; Medicinal Plants; Covid-19.